Spiritual Intelligence of the Trainee Teachers in Kolkata: The Influence of Gender, Academic Stream, and Family Structure - Rout, Bimla; Sarkar, Prakriti Ranjan (JOURNAL OF INDIAN EDUCATION, 2026)
This study examined the Spiritual Intelligence (SI) of trainee teachers in Kolkata District, West Bengal, focusing on the influence of gender, family structure, and academic stream. A standardised Spiritual Intelligence Scale was administered to a sample of 110 trainee teachers (74 females, 36 males) from various teacher training institutions. Data were analysed using descriptive statistics, Mann Whitney U test and Kruskal Wallis test via MS Excel 2019 and SPSS version 25. Results revealed that 67.3 per cent of participants demonstrated an average level of SI. A statistically significant gender difference was found, with males scoring higher on SI (p < 0.05). No significant differences emerged based on family structure or academic stream (p > 0.05). These findings suggest that while gender influences SI, family background and academic specialisation do not. The study contributes to understanding SI in teacher education and highlights the importance of gender-sensitive approaches in fostering spiritual development in teacher training programmes.